Granzyme A is critical for recovery of mice from infection with the natural cytopathic viral pathogen, ectromelia. - Müllbacher, A (1996)
Cytolytic lymphocytes are of cardinal importance in the recovery from primary viral infections. Both natural killer cells and cytolytic T cells mediate at least part of their effector function by target cell lysis and DNA fragmentation. Two proteins, perforin and granzyme B, contained within the cytoplasmic granules of these cytolytic effector cells have been shown to be directly involved in these processes. A third protein contained within these granules, granzyme A, has so far not been attributed with any biological relevance. Using mice deficient for granzyme A, we show here that granzyme A plays a crucial role in recovery from the natural mouse pathogen, ectromelia, by mechanisms other than cytolytic activity.